Production and Nutritional Evaluation of High Energy/Protein Meal (‘Danwake’) from Wheat, Cowpea, Bambara Groundnut and Cassava - Fusam S. K; Modu S.; Laminu, H. H; Chamba G.; Bintu B. P. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Traditional food system is all food from a particular culture produced from locally available and highly nutritious sources which are culturally accepted by the people. It includes socio cultural meanings, acquisition, processing techniques, usage, composition and nutritional consequences for people using the food. This work aimed at the quality evaluation of different high energy/protein meal (‘danwake’) formulated from blends of germinated wheat, dehulled cowpea and dehulled Bambara groundnut, and Fermented cassava flour. Germinated wheat, dehulled cowpea and bambara groundnut, fermented cassava, baobab leaves (kuka) and potash (kanwa) were incorporated in the proportion of 70:17:4:4:3.5:1.5 for composite ‘danwake’ flour test 1 Aa. The ratios 60:15:5: 16:3:1 is for composite flour test 2 Bb, 9:18:9:60:3:1 for composite ‘danwake’ flour test 3 Cc respectively. A control ‘danwake’ flour wheat flour 100% (WWF) and cassava flour 100% (CCF) served as control. Proximate, mineral, vitamins, amino acid profile, in vitro protein digestibility and anti-nutritional factors were analyzed. Proximate analysis showed that formulated composite ‘danwake flours’ have 363.24Kcal, 363.62 Kcal, and 350.43 Kcal for Aa, Bb, and Cc respectively for total energy, 17.35 %, 18.92 %, and 12.86 % protein contents for Aa, Bb, and Cc respectively, 68.67 %, 65.28 %, 69.08 % carbohydrate contents for Aa, Bb, and Cc respectively. Moisture contents ranged between (6.42-7.11) percent, with the blend with 60% wheat flour has the least moisture contents of 6.40%. All the formulations including the commercial flours contained the following vitamin range (0.08-0.1 ug/g) thiamine, (0.02-0.05 ug/g) riboflavin, (0.11-0.16 ug/g) cyanocobalamine, (0.08-0.40 ug/g) ascorbic acid and (0.01-0.02 ug/g) vitamin A, while the mineral element range (0.02-0.26 mg/100g) Cr, (0.14-0.76 mg/100g) Zn, (0.64-1.75 mg/100g) Fe, (0,97 1.77mg/100g) Ca, and (0.15-0.51 mg/100g) Mn. Amino acid Lysine, Asphatic acid and Glutamic acid, Alanine, Methionine and Phenylalanine were higher in ‘danwake’ blend Bb. Norleucine was not detected in all the samples. The formulated composite ‘danwake’ flours were superior to control in terms protein content, vitamins and mineral element levels. The composite ‘danwake’ flours, Bb is more nutritious followed by Aa, while Cc is the least in terms of mineral element levels, vitamins and amino acid.